KRITIK IDEOLOGIS DALAM NARASI SEJARAH ORDE BARU: ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH PADA BUKU TEKS IPS KELAS IX KEMENDIKBUD - Ummami Riza; Nailul Fauziyah (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2025)
This research focuses on how the author narrates the political, economic, and social life development of the community in the New Order historical material in the Social Science Class IX textbook, as well as how the results of writing the New Order historical theme are reviewed from the perspective of critical discourse analysis of the Norman Fairclough model. This study uses a qualitative descriptive method with data sources in the form of Class IX Social Sciences textbooks. The data collection technique was carried out through documentation and interviews, with the researcher as the main instrument. The data analysis uses the Norman Fairclough model critical discourse analysis approach, which includes text analysis, discourse practice, and sociocultural practice. The results of the study show that the writing of content about political, economic, and social life developments during the New Order period in the textbook contains bias against certain interests. An unbalanced selection of facts indicates the existence of framing that favors certain parties. Although the author has no specific political affiliation, the references used are controversial regarding the truth of historical facts. In addition, framing in textbooks is done consciously, influenced by the author's background growing up in the government environment.